Studi Potensi Sekam Padi Sebagai Bahan Bakar Pemakaian Rumah Tangga Sebagai Alternatif Pengganti LPG di Kabupaten Konawe Selatan - M, Saiful .; Balaka, Ridway; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2023)
Energy is a fundamental need that is increasing every year. Dependence on fossil fuels, such as limited LPG and an increasingly threatened environment encourages the development of renewable energy sources. This study aims to examine the feasibility of rice husk energy potential as an alternative fuel to replace LPG in the South Konawe Regency. A survey was conducted to determine the pattern of rice husk utilization at the community level at several rice milling locations in South Konawe Regency. Data analysis was carried out using data obtained from BPS Southeast Sulawesi and BPS Konawe Selatan Publications (2018-2022). By calculating the estimated energy potential of rice husks and energy consumption of LPG use, and forecasting until 2025 using the Double Exponential Smoothing method from Holt. The results of the data analysis show that the average energy potential of rice husks (2018-2022) is 236,124.56 (GJ), and LPG energy consumption (2018-2022) is 365,625.83 (GJ). For forecasting the energy potential of rice husks in 2025 amounting to 277,863.22 (GJ), and forecasting LPG energy consumption in 2025 of 363,968.39 (GJ). In conclusion, the energy potential of rice husks can distribute around 65% of the total LPG energy needs of households in South Konawe Regency. Keywords: Biomass, renewable energy, rice husks